Geniposide Ameliorates Liver Fibrosis Through Reducing Oxidative Stress and Inflammatory Respose, Inhibiting Apoptosis and Modulating Overall Metabolism - Lu Yang; Lu Yang; Liping Bi; Lulu Jin; Yuming Wang; Yuting Li; Yuting Li; Zixuan Li; Wenju He; Huantian Cui; Jing Miao; Li Wang (Frontiers in Pharmacology, 2021)
Liver fibrosis is a progressive liver damage condition caused by various factors and may progress toward liver cirrhosis, and even hepatocellular carcinoma. Many studies have found that the disfunction in metabolism could contribute to the development of liver fibrosis. Geniposide, derived from Gardenia jasminoides J. Ellis, has been demonstrated with therapeutic effects on liver fibrosis. However, the exact molecular mechanisms of such liver-protection remain largely unknown. The aim of this study was to explored the effect of geniposide on metabolic regulations in liver fibrosis. We used carbon tetrachloride (CCl4) to construct a mouse model of liver fibrosis and subsequently administered geniposide treatment. Therapeutic effects of geniposide on liver fibrosis were accessed through measuring the levels of hepatic enzymes in serum and the pathological changes in liver. We also investigated the effects of geniposide on inflammatory response, oxidative stress and apoptosis in liver. Furthermore, serum untargeted metabolomics were used to explore the metabolic regulatory mechanisms behind geniposide on liver fibrosis. Our results demonstrated that geniposide could reduce the levels of hepatic enzymes in serum and ameliorate the pathological changes in liver fibrosis mice. Geniposide enhanced the activities of superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) and decreased methane dicarboxylic aldehyde (MDA) levels in liver. Geniposide treatment also decreased the levels of interleukin (IL)-6, IL-1β, and tumor necrosis factor-alpha (TNF-a) in liver tissue homogenate. Terminal deoxynucleotidyl transferase-mediated dUTP-biotin nick end labeling assay (TUNEL) staining demonstrated that geniposide could reduce the apoptosis of hepatocytes. Geniposide increased the protein expression of B-cell lymphoma-2 (Bcl-2) and downregulated the protein expression of Bcl-2 Associated X (Bax), cleaved-Caspase 3, and cleaved-Caspase 9. Serum untargeted metabolomics analysis demonstrated that geniposide treatment improved the metabolic disorders including glycerophospholipid metabolism, arginine and proline metabolism, and arachidonic acid (AA) metabolism. In conclusion, our study demonstrated the protective effects of geniposide on liver fibrosis. We found that geniposide could treat liver fibrosis by inhibiting oxidative stress, reducing inflammatory response and apoptosis in the liver, and modulating glycerophospholipid, and arginine, proline, and AA metabolism processes.